PENGEMBANGAN MEDIA LUDO MATH GAME DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PESERTA DIDIK KELAS V SD - Firda Yulianti; Astri Sutisnawati; Din Azwar Uswatun (Jurnal Pendidikan Dasar, 2020)
This research is an R and D research. The product developed was a ludo math game learning media using the Borg and Gall research design adapted by Sugiyono but the design used is only seven steps as follows: 1) Potential and problem step 2) Data collection step 3) Product design step 4) Design validation step 5) Design revision step 6) Product trial step 7) Product revision step. The purpose of this research is to describe the feasibility of ludo math game media, Student responses to the media ludo math game and the effectiveness of the ludo math game media on students numeracy skills. It can be concluded with this research that the ludo math game media as a result of the development is feasible to use because the results of the assessment of the developed media are an average value of 47.25 for the aspect of quality of content, an average value of 38.75 for the instructional quality aspect, an average value of 88.00 for aspects of technical quality with very good criteria. Based on the results of student r responses to the media ludo math game average value of 97,86 for the aspect of quality of content, an average value of 98,78 for the instructional quality aspect, an average value of 99,17 for aspects of technical quality with very agree criteria. There is an increase in the value of pretest to posttest using the gain score of 0.83 which is included in the high criteria.